(-2,10) , (2,-10)

Slope is equal to the change in y over the change in x, or rise over run.

m=change in ychange in x

The change in x is equal to the difference in x-coordinates (also called run), and the change in y is equal to the difference in y-coordinates (also called rise).

m=y2-y1x2-x1

Substitute in the values of x and y into the equation to find the slope.

m=-10-(10)2-(-2)

Simplify.

Reduce the expression by cancelling the common factors.

Cancel the common factor of -10-(10) and 2-(-2).

Rewrite -10 as -1(10).

m=-1⋅10-(10)2-(-2)

Factor -1 out of -1(10)-(10).

m=-1(10+10)2-(-2)

Reorder terms.

m=-1(10+10)2-2⋅-1

Factor 2 out of -1(10+10).

m=2(-1(5+5))2-2⋅-1

Cancel the common factors.

Factor 2 out of 2.

m=2(-1(5+5))2(1)-2⋅-1

Factor 2 out of -2⋅-1.

m=2(-1(5+5))2(1)+2(1)

Factor 2 out of 2(1)+2(–1).

m=2(-1(5+5))2(1+1)

Cancel the common factor.

m=2(-1(5+5))2(1+1)

Rewrite the expression.

m=-1(5+5)1+1

m=-1(5+5)1+1

m=-1(5+5)1+1

Add 5 and 5.

m=-1⋅101+1

m=-1⋅101+1

Simplify the denominator.

Multiply -1 by -1.

m=-1⋅101+1

Add 1 and 1.

m=-1⋅102

m=-1⋅102

Simplify the expression.

Multiply -1 by 10.

m=-102

Divide -10 by 2.

m=-5

m=-5

m=-5

m=-5

Substitute the value of m into the slope-intercept form of the equation, y=mx+b.

y=(-5)⋅x+b

Substitute the value of x into the slope-intercept form of the equation, y=mx+b.

y=(-5)⋅(-2)+b

Substitute the value of y into the slope-intercept form of the equation, y=mx+b.

10=(-5)⋅(-2)+b

Rewrite the equation as (-5)⋅(-2)+b=10.

(-5)⋅(-2)+b=10

Multiply -5 by -2.

10+b=10

Move all terms not containing b to the right side of the equation.

Subtract 10 from both sides of the equation.

b=10-10

Subtract 10 from 10.

b=0

b=0

b=0

The values of the slope and y-intercept are m=-5 and b=0.

m=-5

b=0

Find the Slope and Y-Intercept (-2,10) , (2,-10)